2001
DOI: 10.2460/javma.2001.218.1771
|View full text |Cite
|
Sign up to set email alerts
|

Development of a complete electronic medical record in an academic institution

Abstract: I n veterinary medicine a complete electronic medical record (EMR) should contain all information (eg, demographic, financial, medical/surgical, diagnostic, and pharmaceutical) related to all visits of a patient as well as owner contact and billing information. It is clear that such a complete EMR and the ability to retrieve and use the information it contains in an integrated manner would provide operational economies, improve patient care, and enhance teaching. We embarked on a project to develop such a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The ‘Independent Inquiry into Dog Breeding’ report cited primary-care practice electronic clinical data using standardised coding of diagnoses as the optimal data source for reliable prevalence estimation [ 7 ]. However, early attempts at large-scale electronic surveillance struggled to cope with the large volumes of clinical data collected [ 19 ] and initial veterinary PMSs did not enforce structured coding systems [ 97 ], although there is now evidence that practising veterinarians accept a clinical rationale for standardised data recording [ 98 , 99 ].…”
Section: Reviewmentioning
confidence: 99%
“…The ‘Independent Inquiry into Dog Breeding’ report cited primary-care practice electronic clinical data using standardised coding of diagnoses as the optimal data source for reliable prevalence estimation [ 7 ]. However, early attempts at large-scale electronic surveillance struggled to cope with the large volumes of clinical data collected [ 19 ] and initial veterinary PMSs did not enforce structured coding systems [ 97 ], although there is now evidence that practising veterinarians accept a clinical rationale for standardised data recording [ 98 , 99 ].…”
Section: Reviewmentioning
confidence: 99%
“…Unfortunately the different methods described here utilised to obtain veterinary data are not necessarily transferrable across these PMSs due to differences in database structure. There are many different commercial PMSs on which information from veterinary primary care consultations is kept [ 2 , 4 , 16 ]. Therefore it is a challenge to obtain and link data from different PMSs representative of all systems currently in use within veterinary practice.…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, an ideal EMR system has efficient search and retrieval capabilities, uses standardized diagnostic coding, and protects patient and client confidentiality while maximizing patient health, quality of care, practice efficiency, and profit. 14 However, few EVMR models with these capabilities exist in the veterinary medical profession; these include proprietary systems in use by large networks of hospitals, a systems used by veterinary medical teaching hospitals, 1 and commercial programs employed by independent clinics and hospitals. b–e …”
mentioning
confidence: 99%
“…17 Electronic veterinary medical record systems available to the veterinary medical profession are believed to include some of these capabilities, although they have not been described as specifically having or lacking these functions. 1,10,13,14 Receiving greater attention recently, however, is the potential of EVMRs to contribute to understanding the epidemiology of animal diseases, including those that have zoonotic potential. 18 A comprehensive literature review in 2001 found that 868 of 1,415 (61%) infectious human pathogens were zoonotic and 132 of 175 (75%) pathogenic species associated with EIDs were zoonotic.…”
mentioning
confidence: 99%